#TITLE_ALTERNATIVE# - HANUM AMAHORU (NIM : 12909035); pembimbing: Dr.rer.nat. Dadang Kurniadi Mihardja ; Dr. Ir., AFIFAH
In this thesis has been analyzed imagery satellite data from Landsat-7 ETM+ to calculate the alteration rate of sedimentation area and its pattern in the Jakarta Bay with the Ambarwulan et. al algorithm. The calculation results have been compared with field data in the coastal waters of Muara Karang, North Jakarta and Muara Tawar, North Bekasi. The mean relative error of Total Suspended Solid (TSS) from June 2010 and August 2011 that represents East Monsoon compared to observed data on 14th August 2010 in the coastal waters of Muara Karang is 5,875%, while the error on October 2011 that represents Transition Monsoon II compared to measured data on 15th November 2010 in the Muara Tawar coastal waters is 12%. Analysis results shown high TSS between 83 – 183 mg/liter at the surrounding of the estuaries of some rivers flowing to the Jakarta Bay, while the alteration of sediment coverage area at Muara Karang coastal waters were decreased by 20,1, 21,3, and 32 km2 in the periode of April 22 - May 8 , August 12 – 28, August 28 – September 13, 2011 and increased by 26,1 km2 in range time May 8 - June 9, 2010 and 35,6 km2 between April 6 – 22, 2011. Sediment concentration changes at both location were increased by 0,04, 0,0272 and 0,006 kg/m3 in April 6 – 22, 2011, May 21 and June 22, 2010 and August 12 - 28, 2011, while in time period April 22 – May 8, 2011 and August 28 – September 13, 2011 the concentratios were decreased by 0,02 and 0,271 kg/m3. In the west monsoon sediment accumulations were occurred at the eastern side of Jakarta Bay and at the western coast of Muara Karang, while in the east monsoon sediment are accumulated in the western side of the bay. In transition monsoon I and II sediments were spread along the Jakarta Bay coastal waters.